Hydrocracking of Calophyllum inophyllum Oil With Non-sulfide CoMo Catalysts - Rismawati Rasyid; Adrianto Prihartantyo; Mahfud Mahfud; Achmad Roesyadi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
This research was aimed to convert Calophyllum inophyllum kernel oil into liquid fuel through hydro-cracking process using non-sulfide CoMo catalysts. The experiment was carried out in a pressurized re-actor operated at temperature and pressure up to 350 oC and 30 bar, respectively. The CoMo catalysts used in the experiment were prepared by 10 wt.% loading of cobalt and molybdenum solutions over various supports, i.e. γ-Al2O3, SiO2, and γ-Al2O3-SiO2 through impregnation method. It is figured out from the experiment that non-sulfide CoMo based catalysts have functioned well in the hydrocracking conversion of Calophyllum inophyllum kernel oil into fuels, such as gasoline, kerosene, and gasoil. The CoMo/γ-Al2O3 catalyst resulted higher conversion than CoMo/SiO2 and CoMo/γ-Al2O3-SiO2. The fuel yields were 25.63% gasoline, 17.31% kerosene, and 38.59% gasoil. The fuels obtained in this research do not contain sulfur compounds so that they can be categorized as environmentally friendly fuels. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)